The influence of service climate, identity strength, and contextual ambidexterity upon the performance of public organizations - Nunes, F. G. (2018)
Improving the performance of public organizations has become a major concern among researchers and managers, rendering the search for the factors that distinguish the best performers a fundamental endeavor. Despite the abundant empirical research conducted about this topic, there are still inconsistencies in how management and other organizational elements determine organizational performance, calling for more theory-oriented research. In this paper, we join this line of reasoning and suggest that service climate, organizational identity strength, and contextual ambidexterity, variables coming from very different theoretical traditions, predict the performance of public organizations, as perceived by their members. In order to test this proposition, we surveyed a sample of 618 civil servants working for two different organizations. In this survey, we included measures of the three predictors (service climate, organizational identity strength, and contextual ambidexterity) and the variable of interest (organizational performance). Using hierarchical regression analysis, we found evidence supporting a positive relationship between organizational performance and service climate, identity strength, and especially, contextual ambidexterity, with some differences between the two organizations regarding the intensity of these relationships. Besides contributing to broadening the discussion about the antecedents of public organizations’ performance, this study also supports the validity of the three theoretical perspectives. Considering the management of public organizations, our study challenges managers to play a fundamental role in orchestrating routines and work practices that allow configuration of the most relevant organizational capacities leading to better performance.